Intermittent Hypoxia Induces Autophagy to Protect Cardiomyocytes From Endoplasmic Reticulum Stress and Apoptosis - Chang, Jui-Chih; Hu, Wei-Fen; Lee, Wen-Sen; Lin, Jian-Hong; Ting, Pei-Ching; Chang, Huai-Ren; Shieh, Kun-Ruey; Chen, Tsung-I; Yang, Kun-Ta (Frontiers in Physiology, 2019)
Intermittent hypoxia (IH) characterized as cyclic episodes of short period hypoxia followed by normoxia occurs in many physiological and pathophysiological conditions, such as pregnancy, athlete, obstructive sleep apnea and asthma. Hypoxia can induce autophagy, which is activated in response to protein aggregates, in the proteotoxic forms of cardiac diseases. Previous studies suggested that autophagy can protect cells by avoiding accumulation of misfolded proteins, which can be generated in response to ischemia/reperfusion (I/R) injury. The objective of the present study was to determine whether IH-induced autophagy can attenuate endoplasmic reticulum (ER) stress and cell death. In this study, H9c2 cell line, rat primary cultured cardiomyocytes and C57BL/6 male mice underwent IH with an oscillating O2 concentration between 4 % and 20 % every 30 min for 1–4 days in an incubator. The levels of LC3, an autophagy indicator protein, and CHOP and GRP78 (ER stress-related proteins) were measured by Western blotting analyses. Our data demonstrated that the autophagy-related proteins were upregulated in 1-3 day, while the ER stress-related proteins were downregulated in second day after IH. Treatment with H2O2 (100 µM) for 24 h caused ER stress and increased the level of ER stress-related proteins, and these effects were abolished by pre-treatment with IH condition. In response to the autophagy inhibitor, the level of ER stress-related proteins was upregulated again. Taken together, our data suggested that IH could increase myocardial autophagy as an adaptive response to prevent the ER stress and apoptosis.